The Use of RAPDs Technique for the Detection of Genetic Stability of Date Palm Plantlets Derived From In Vitro Culture of .Inflorescence - Saleh Bader; Michael Baum; Hussam Khierallah; Wafaa Choumane (College of Education for Pure Sciences, 2007)
The study aimed to use of RAPD - PCR markers to prove the genetic stability of two date palm (Phoenix dactylifera L.) cultivars Barhi and Maktoom produced by tissue culture technique. Inflorescences were excited from adult tree of the two cultivars. Spadixes were divided in to pieces . 0.5 em in length and cultured on MS modified medium supplemented with 100 !lM of 2,4-D and 15 !lM of 2ip. Callus was obtained after 8 weeks and adventitious shoots formation was achieved when callus transferred to MS modified medium supplemented with 10 !lM of 2ip and 5 jlM of NAA. Shoots rooted on half strength MS salts medium supplemented with 5 !lM of NAA with increasing sucrose concentration to 131.5 mM. Plantlets were acclimatized and successfully transferred to soil. RAPD - PCR analysis using 25 universal primers were_performed on DNA extracted from the fresh healthy leaves of the mother tree and from samples randomly taken plantlets derived from tissue culture. Reproducible RAPD patterns were obtained using 20 primers, Seventeen primers showed completely monomorphic bands in all samples tested of the progeny. Only three primers showed some polymorphic bands on the agarose gel for both cultivars in some samples tested comparing with the DNA banding pattern for the intact trees, these were OPD.01 primer for Barhi, and OPB.07 and OPC.08 for Maktom. According to the results above it was obvious that genetic variations could occurred in plantlets derived from callus proliferated from inflorescence of date palm, furthermore RAPD appears to be an efficient technique and a simple fast DNA marker for the early detection of genetic variations in plants propagated by tissue culture technique.